Learn Rights: A Gamified Ai-Powered Platform For Legal Literacy And Children’s Rights Awareness In India - Srilatha, Mrs. A.; Rani, R. Usha; Yadav, Reethu; Reddy, Ruchitha; Sathwika, Laxmi; Krishna, N. Bhargav (Metallurgical and Materials Engineering, 2025)
Children’s rights should be acknowledged within the contemporary educational environment in an effort to create well-informed and accountable citizens. In this study, the creation of a gamified platform with the aim of improving legal literacy among Indian children is presented. Through the gaming and interactive narrative components, the gamified platform educates children on their rights. With the additional incorporation of an AI assistant that offers real-time answers to queries on the rights of the child. The software delivers an engaging learning processby combining the principles of child psychology, law education, and gamification. Research methodology involved user testing, iterative design cycles, and an extensive literature review, all of which ensured the effectiveness and flexibility of the platform. The results show outstanding improvements in children’s understanding of their rights, showcasing the gamification and artificial intelligence functionality in law education. The piece ends with suggestions for further enhancement and widespread platform application.